Miniature multi‐band monopole antenna using spiral ring resonators for radiation pattern characteristics improvement. Issue 6 (1st March 2013) - Wan, Y.‐T.; Yu, D.; Zhang, F.‐S.; Zhang, F.
Abstract : A compact coplanar waveguide (CPW)‐fed multi‐band monopole antenna loaded with spiral ring resonators is presented. The proposed antenna consists of two spiral ring strips which are printed on the different sides of the substrate and connected through a via‐hole. The size of the miniaturised antenna is only about 27.5 × 20 × 1 mm 3 . The proposed antenna can excite multi‐resonant modes close to the 2.5/3.5/5.5 GHz bands to meet the specifications of the worldwide interoperability for microwave access (WiMAX) system. By introducing the spiral ring structure, very good radiation pattern characteristics can be obtained. With a figure‐of‐eight pattern in the E‐plane and omnidirectional pattern in the H‐plane, measured peak gains are about 2.0/2.23/2.58 dBi at the 2.5/3.5/5.5 GHz operating bands, respectively.